President Joko Widodo's Communication Style Faces Hate Speech In Online Media For The 2019-2024 Period - Sutrisno, Sutrisno (Jurnal Mamangan, 2025)
Hate speech on social media is a growing concern that threatens social harmony and political stability in Indonesia. While prior studies mostly examine legal and technological aspects, limited attention is given to leaders’ communication styles and their cultural foundations. This study analyzes President Joko Widodo’s communication style in responding to hate speech on social media during 2019–2024, with emphasis on Javanese philosophical values. A qualitative case study was conducted through analysis of official documents, presidential speeches, social media content, policy texts, and related literature, applying thematic analysis to identify communication patterns and cultural elements. The findings indicate that Jokowi’s communication emphasizes inclusiveness, public education, and digital literacy promotion. His responses prioritize constructive dialogue and avoid emotional reactions, framed within Javanese values such as tepo sliro and mikul dhuwur mendhem jero. These approaches help reduce hate speech escalation and reinforce public trust and cohesion. Jokowi’s culturally rooted communication strategy effectively mitigates hate speech while fostering unity in Indonesia’s diverse society. Practically, the study offers guidance for policymakers and leaders to integrate cultural values into digital-era communication strategies. Theoretically, it contributes to political communication studies by showing the role of local philosophy in shaping leadership responses to online challenges.